Yale observation scale for bacterial infection in febrile children - Mangla, Shiwani; Jain, Hemant (International Journal of Contemporary Pediatrics, 2020)
Background: Sepsis is one of the leading causes of mortality in children under 5 years by UNICEF statistics which is difficult to diagnose because of nonspecific initial clinical presentation and potential for rapid deterioration. In this regard use of Yale Observation Scale assists in early recognition of serious bacterial infection than other laboratory investigation as it is simple, quick, easy to apply and cost-effective bed side scale. Methods: All eligible young febrile infants and children were consecutively enrolled in the study. Axillary temperatures of the cases were documented. Yale observation scoring was done. Blood sample were sent for culture and sensitivity. Colonies were identified morphologically by Gram stain and biochemically. The collected data was analyzed using ROC curve for finding cut off scores of Yale Observation Scale for prediction of severe bacterial illness and final outcome. Statistical analysis was performed using the Statistical Packages for Social Sciences (SPSS) version 14 for MS Window. Results: Bacteremia was found in 23(15.3%) out of total 150 young febrile children enrolled in the present study. It shows that in lower YOS score blood culture was sterile and in higher YOS score blood culture was positive for bacteremia, which is statistically significant with p value (<0.05). As per ROC curve analyses the best cut off value of YOS for prediction of bacteremia was 17.5 with sensitivity 91.3%, specificity 81.9%, PPV 47.7% and NPV of 98.1%. Conclusions: YOS of >17.5 has a good predictive ability for prediction of bacteraemia in young febrile children.